32n
3 x 23n - 1
2n
6
1
Correct answer is D
62n+1×9n×42n18n×2n×122n = (2×32n+1×32n)×24n(2×9)n×2n×(6×22n)
= (22n+1×32n+1)×32n×24n2n×32n×2n×24n×32n
= 22n+1+4n×32n+1+2n2n+n+4n×32n+4n×32n+2n
= 26n+1×34n+126nx34n
= 26n + 1 - 6n x 34n + 1 - 4n
2 x 3 = 6
P(-6, 1) and Q(6, 6) are the two ends of the diameter of a given circle. Calculate the radius. ...
Find the quadratic equation whose roots are -12 and 3...
Find the gradient of the line passing through the points (-2, 0) and (0, -4)...
In the figure, TZ is tangent to the circle QPZ. Find x if TZ = 6 units and PQ = 9 units ...
Simplify without using tables log26log28 - log232log212...